The Use of Practical Video Demonstration for Class VII Photosynthetic Materials to Stimulate Basic Science Process Skills - Donny Auliya Arrohman; Normalia Sandy Palumpun; Jumadi Jumadi; Zuhdan Kun Prasetyo (Postgraduate, University of Mataram, 2021)
Science process skills are one of the most important skills to be mastered by every student. These skills will teach and train students to conduct an investigation or scientific discovery. Science process skills consist of two main groups, namely basic and integrated science process skills. The research carried out here focuses on basic science process skills. This research aims to see how photosynthetic material practicum demonstration videos for class VII stimulate. The type of research used in this study is descriptive analysis, with the sample used as many as 17 students spread out in one class, namely class VIIF. The data collected consists of qualitative data and quantitative data. Qualitative data was obtained when researchers conducted interviews and observations of students, while quantitative data was obtained through the results of pretest and posttest basic science process skills. The results showed that overall, students experienced an increase in the percentage of achievement of each aspect of basic science process skills (observing from 67.65 to 85.29%, classifying from 85.29 to 94.12%, measuring from 78.43 to 88.24%, inference from 52.94 to 70.59%, predicting from 76.57 to 88.24%, and communicating from 82.35 to 94.12%). Other results obtained in this study are several obstacles when the online learning process is carried out, namely the instability of the internet network, insufficient time to conduct video conferencing, and some who experience slow video running